2012
DOI: 10.1111/j.1466-7657.2012.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric resuscitation for nurses working in Ghana: an educational intervention

Abstract: Policy makers in Ghana need to consider implementing education programmes in paediatric resuscitation for nurses as part of a comprehensive strategy to improve emergency systems and address preventable and avoidable infant and child mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Multiple studies reported the importance of continuing nursing education to empower nurses to perform at high levels within their duties and take leadership roles both explicitly in training and implicitly through acquisition of skills and knowledge. Specifically, the discussion focused on the insufficiency of solely instilling knowledge or skills in nurses, but that it was necessary to also develop a sense of motivation and self-efficacy in performing tasks and implementing changes in their day-to-day work 42–44. For example, Brennan et al showed increased self-efficacy through self-reported measures in 41 nurses in conjunction with increased knowledge on intubation methods 44.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies reported the importance of continuing nursing education to empower nurses to perform at high levels within their duties and take leadership roles both explicitly in training and implicitly through acquisition of skills and knowledge. Specifically, the discussion focused on the insufficiency of solely instilling knowledge or skills in nurses, but that it was necessary to also develop a sense of motivation and self-efficacy in performing tasks and implementing changes in their day-to-day work 42–44. For example, Brennan et al showed increased self-efficacy through self-reported measures in 41 nurses in conjunction with increased knowledge on intubation methods 44.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the discussion focused on the insufficiency of solely instilling knowledge or skills in nurses, but that it was necessary to also develop a sense of motivation and self-efficacy in performing tasks and implementing changes in their day-to-day work 42–44. For example, Brennan et al showed increased self-efficacy through self-reported measures in 41 nurses in conjunction with increased knowledge on intubation methods 44. One study recognised the importance of empowerment especially when training for task shifting, which is defined as the delegation of tasks to less specialised health workers 45.…”
Section: Resultsmentioning
confidence: 99%
“…The GEHIP program trained midwives at the sub-district and village levels in neonatal resuscitation using a bag and mask to prevent birth asphyxia [ 20 24 ]. GEHIP implemented a policy of consistent partograph [ 25 27 ] use and clinical trainings to support this new policy, given identified challenges to proper use [ 25 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Partnering for curricula adaptation will enable training faculty and maximize sustainability ( 52 ). An excellent example of a partnership encompassing international HIC guidelines with local adaptations is the ETAT course which has resulted in improved outcomes in LMICs ( 54 ). There remains the challenge of measuring the impact of these trainings in regard to sustained changes in care patterns and improved outcomes in LMIC ( 52 , 55 ).…”
Section: Trainingmentioning
confidence: 99%